PROPOSED BUSINESS STRATEGY FORMULATION AND IMPLEMENTATION FOR RISMA F MART TO INCREASE OPERATIONAL PERFORMANCE - Nurfitria/ 29116226, Rosa
Risma F Mart is a retail business consentrate in hajj and umroh equipment and souvenir. Risma F Mart located in Pasar Baru Trade Center Bandung and currently has 2 branches. The company established in 1995. Risma F MartÃ‚Â’s performance was not so great, the owner is exhausted to operate the business. Because the administration still manual, they need to handle it everyday. This research interest on developing business strategy for Risma F Mart to improve the performance. The analysis starts from an environmental analysis consisting of internal and external analysis. BMC (Business Model Canvas), STP analysis (Segmenting, Targeting and Positioning) and Marketing mix 4P, these analysis used to analize internal environment. PEST analysis (Political, Economic, Socio-cultural and Technological) and Porter five forces used to analize external environment. The problem arise from this analysis is that Risma F Mart has a weak competitive position while competing in rapid market growth. There are some internal problems in Risma F Mart need fixing such as lack of merchandise, lack of competent people, lack of administrative management, lack of logistics and common products. SWOT analysis (Strengths, Weaknesses Opportunities, Threats) used to observe external and internal marketing environment, and root problem analysis used to identify the root cause of the problem. There are some problems, which has occurred because lack of administration. SFAS matrix (Strategic Factor Analysis Summary) used to manage external and internal factors into commonly accepted categories of SO (Strength Opportunity), WO (Weakness Opportunity), SO (Strength Treat), WO (Weakness Treat). The analysis include business formulation analysis for strategic planning or long term planning in solving problems, TOWS strategy (threats, opportunities, weaknesses and strength) used to generate a range of possible strategies and implementation strategies.. There are three kinds of strategies proposed to Risma F Mart. First, based on the company's strategy analysis, Risma F Mart can pursue retrenchment strategies for their poor performance. Second, Based on business strategy for Risma F Mart is focusing on cost leadership and differentiation and the last is based on functional strategy, the company can pursue focusing on operating strategy and human resource management strategy. In addition, there are implementation plans for each strategy.